Review of Echocardiographic Findings in Patients with Obstructive Sleep Apnea. (18th November 2018) - Sascău, Radu; Zota, Ioana Mădălina; Stătescu, Cristian; Boișteanu, Daniela; Roca, Mihai; Maștaleru, Alexandra; Leon Constantin, Maria Magdalena; Vasilcu, Teodor Flaviu; Gavril, Radu Sebastian; Mitu, Florin
Abstract : Obstructive sleep apnea (OSA) causes recurrent apneas due to upper respiratory tract collapse, leading to sympathetic nervous system hyperactivation and increased cardiovascular risk. Moderate and severe forms of obstructive sleep apnea are associated with increased atrial volumes and affect left ventricular diastolic and then systolic function. Right ventricular ejection fraction can be accurately assessed via three-dimensional echocardiography, while bidimensional imaging can only provide a set of surrogate parameters to characterize systolic function (tricuspid annulus plane systolic excursion, right ventricular fractional area change, and lateral S'). Tissue Doppler imaging is a more sensitive tool in detecting functional ventricular impairment, but its use is limited by angle dependence and the unwanted influence of tethering forces. Two-dimensional speckle tracking echocardiography is considered more suitable for the assessment of ventricular function, as it is able to distinguish between active and passive wall motion. Abnormal strain values, a marker of subclinical myocardial dysfunction, can be detected even in patients with normal ejection fraction and chamber volumes. The left ventricular longitudinal strain is more affected by the presence of obstructive sleep apnea than circumferential strain values. Although the observed OSA-induced changes are subtle, the benefit of a detailed echocardiographic screening for subclinical heart failure in OSA patients on therapy adherence and outcome should be addressed by further studies.